Phylogeny and taxonomic classification to subgeneric level of Augochloropsis (Hymenoptera: Halictidae) - Celis, Cindy Julieth (2017)
Augochloropsis Cockerell, 1897b is a highly diverse group in the Neotropics and commonly collected in wildlife surveys. These bees remain mostly unidentified in collections because of the lack of taxonomic keys and the incomplete original descriptions, which prevent sorting specimens even at the subgeneric level. The aim of this study was to perform the phylogeny and the taxonomic revision of the genus Augochloropsis to subgeneric level, based on a detailed examination of 56 morphological characters of 2 433 specimens. Four subgenera are recognized and described in detail: (Augochloropsis s.str. (Cockerell, 1897b) (Paraugochloropsis Schrottky, 1906 ((Glyptochlora Moure, 1958) (Glyptobasia (Moure, 1941)))). Photographs of external morphological characters, illustrations of the male genital capsule and the metasomal sterna SIII-SVIII are provided, as well as a taxonomic key to subgenera and distribution maps.